Preparation method of heat-resistant and corrosion-resistant adhesive film and film-coated plate

By adsorbing porous carbon into the coating sheet material and modifying it with other materials, the dispersion performance of porous carbon in the resin matrix and the binding performance of the hot melt adhesive layer are improved, and the problem of poor bonding of porous carbon and resin matrix in the prior art is solved, and higher thermal conductivity and heat resistance are achieved.

CN119592254APending Publication Date: 2025-03-11SUMITOMO ELECTRIC OPTICAL FIBER & CABLE SHENZHEN CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510028181.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing coating sheet materials have shortcomings in terms of heat resistance and corrosion resistance, especially the poor bonding of porous carbon materials with resin matrix, resulting in poor thermal conductivity and heat resistance of the film layer.

Method used

Modified styrene butadiene rubber is prepared by adsorbing the porous carbon to support curcumin and reacting it with styrene butadiene rubber, perfluorooctylethylacrylate, and furfuryl alcohol methacrylate to improve the dispersion performance of porous carbon in the resin matrix. At the same time, the porous carbon loaded with curcumin is introduced into the hot melt adhesive layer to form a thermal conductivity network to improve the thermal conductivity and heat resistance of the film layer.

Benefits of technology

It significantly improves the thermal conductivity and heat resistance of the film layer, forms a stronger thermal conductivity network and better bonding performance, and improves the overall performance of the film plate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a preparation method of a heat-resistant and corrosion-resistant adhesive film and a film-coated plate, the adhesive film comprises a film layer and a hot melt adhesive layer, and the film layer is prepared from the following materials in parts by mass: 40-60 parts of base film resin, 10-20 parts of modified butadiene styrene rubber, 0.5-1 part of an antioxidant and 0.2-0.5 part of a light stabilizer; wherein the modified styrene-butadiene rubber is obtained by reacting styrene-butadiene rubber, perfluorooctyl ethyl acrylate, furfuryl methacrylate and curcumin-loaded porous carbon under the action of an initiator; the hot melt adhesive layer is prepared from the following materials in parts by mass: 10 to 30 parts of modified polyester, 30 to 50 parts of ethylene-vinyl acetate copolymer and 5 to 10 parts of maleic anhydride grafted polyethylene. The curcumin-loaded porous carbon is reacted to obtain the modified styrene-butadiene rubber, the dispersion performance of the porous carbon in a resin matrix can be improved, the porous carbon with good thermal conductivity and high stability is uniformly distributed in a film layer, an effective thermal conductive network is formed to improve the thermal conductivity of the film layer, and thus the heat resistance of the film layer is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of film-coated board materials, and in particular to a method for preparing a heat-resistant and corrosion-resistant adhesive film and a film-coated board. Background Art

[0002] Film-faced plywood is a composite sheet with a layer of film on the surface of the substrate. Specifically, it is usually made by coating an adhesive on the surface of a substrate such as aluminum alloy or steel plate and then covering it with one or more functional films. This type of sheet not only retains the good strength and processing performance of the substrate, but also has the excellent decorative, corrosion-resistant, weather-resistant, and pollution-resistant characteristics of the polymer film. At the same time, it also has the characteristics of being smoke-proof, easy to clean, wear-resistant, moisture-proof, and having a good touch. These characteristics make film-faced plywood widely used in many fields such as architectural decoration, furniture manufacturing, and industrial applications.

[0003] For different substrates such as wood, aluminum plate, gold-plated plate, iron plate, stainless steel plate, etc., requirements are put forward for the bonding performance of the film material and the substrate. At the same time, the properties of the film material itself, such as corrosion resistance, aging resistance, and heat resistance, are direct factors affecting the life of the film material and are also important indicators for achieving substrate protection. CN118667282A discloses an ASA thermal paste composite film and a preparation method thereof, a film-coated plate and a preparation method thereof, and the composite film includes by weight: 40-60 parts of ASA glue powder, 20-40 parts of acrylic resin, 5-10 parts of rutile titanium dioxide, and 1-2 parts of pentaerythritol stearate. This patent increases the dispersion performance of rutile titanium dioxide in numerical values ​​by pentaerythritol stearate, and acrylic resin and rutile titanium dioxide improve the mechanical properties of the composite film. However, rutile titanium dioxide and pentaerythritol stearate are only physically mixed and the bonding may not be strong. CN115570864A discloses a multifunctional film-coated board and a preparation method thereof. The film-coated board comprises an anti-corrosion base film, a metal plate, a hot-melt adhesive film and a polymer waterproof coiled material arranged in sequence, wherein silicon micropowder is added to the polymer waterproof coiled material and the hot-melt adhesive film respectively; the anti-corrosion base film comprises a first base film layer and a second base film layer; the raw materials of the first base film layer comprise maleic anhydride grafted polyethylene, a tackifying resin, silicon micropowder and graphene oxide; the raw materials of the second base film layer comprise a base resin, silicon micropowder and graphene oxide. This patent improves the thermal conductivity of the film material by adding microsilicon powder and graphene oxide. However, the amount of microsilicon powder used is large, and there may be a problem of mismatch with the base resin. Summary of the invention

[0004] In order to solve the problems existing in the prior art, the present invention provides a heat-resistant and corrosion-resistant adhesive film, comprising a film layer and a hot-melt adhesive layer, wherein the material of the film layer comprises, by weight, 40 to 60 parts of a base film resin, 10 to 20 parts of modified styrene-butadiene rubber, 0.5 to 1 part of an antioxidant, and 0.2 to 0.5 parts of a light stabilizer; wherein the modified styrene-butadiene rubber is obtained by reacting styrene-butadiene rubber, perfluorooctyl ethyl acrylate, furfuryl methacrylate, and porous carbon loaded with curcumin under the action of an initiator; The materials of the hot melt adhesive layer include, by weight, 10 to 30 parts of modified polyester, 30 to 50 parts of ethylene-vinyl acetate copolymer, and 5 to 10 parts of maleic anhydride grafted polyethylene.

[0005] Carbon materials include graphene, carbon nanotubes, carbon fibers, porous carbon, etc., which generally have high specific surface area, stability, thermal conductivity and mechanical strength. Among many carbon materials, the preparation method of porous carbon is relatively simple. Some literatures have used organic metal salts to prepare porous carbon with a thin layer structure. The principle is that under a protective gas atmosphere, the organic components of the organic metal salts are carbonized to form a carbon matrix, and the inorganic components are decomposed to form metal oxides. The amorphous carbon formed at a higher temperature has a strong reducing property, which reduces the metal oxides, resulting in in-situ etching of the carbon matrix, forming a rich pore structure. After the carbonization is completed, the inorganic impurities are removed to obtain a porous carbon material with a large specific surface area.

[0006] Although the porous carbon material has more binding sites, its binding property with the resin matrix is ​​still poor, which makes its direct addition not only unable to play its good mechanical strength advantage, but also easy to agglomerate in the structure due to poor dispersibility, and even reduces the strength of the film layer. Curcumin is a natural phenolic antioxidant with unsaturated aliphatic and aromatic groups in the main chain. This allows curcumin to react with unsaturated resin under the action of an initiator. Therefore, the porous carbon is adsorbed and loaded with curcumin, and then reacted, which can improve the dispersion performance of the porous carbon in the resin matrix. The porous carbon with good thermal conductivity and strong stability is evenly distributed in the film layer, which can form an effective thermal conductivity network to improve the thermal conductivity of the film layer, thereby improving the heat resistance of the film layer. At the same time, curcumin also has good antioxidant properties, and can withstand high temperatures for a short time without losing activity. After loading, the porous carbon also has protective properties for curcumin, which makes the film layer have strong heat resistance.

[0007] Perfluorooctyl ethyl acrylate with fluorocarbon bonds, furanyl methacrylate with furan groups, and porous carbon loaded with curcumin were used for reaction modification with styrene-butadiene rubber. The introduction of fluorocarbon bonds is beneficial to improving the temperature resistance of the film layer; the furan group and the benzene ring of the modified polyester in the hot melt adhesive layer have a certain aromatic ring stacking effect, which can improve the bonding performance of the hot melt adhesive layer and the film layer.

[0008] Furthermore, the preparation method of the modified styrene-butadiene rubber comprises, in parts by mass, 30-50 parts of styrene-butadiene rubber are heated and melted, and then 5-10 parts of perfluorooctyl ethyl acrylate, 10-15 parts of furfuryl methacrylate, 2-5 parts of porous carbon loaded with curcumin and 0.5-1.5 parts of initiator are added to react to obtain modified styrene-butadiene rubber.

[0009] Furthermore, the preparation method of the modified polyester comprises, by parts by mass, 10-30 parts of ethyl 3,3-diphenylpropionate, 50-80 parts of versatate vinyl carbonate and 0.2-1 parts of initiator are added to 60-150 parts of the first solvent for polymerization reaction at elevated temperature, and then 60-100 parts of silane monomer and 0.1-0.3 parts of catalyst are added for further reaction at elevated temperature to obtain modified polyester.

[0010] Based on the fact that porous carbon loaded with curcumin can successfully participate in polymerization and addition reactions, porous carbon loaded with curcumin is also introduced when preparing modified polyester. At the same time, a small amount of cobalt ions are introduced during loading, and curcumin can chelate cobalt ions, so that the hot melt adhesive layer formed by the prepared silane monomer has better bonding properties.

[0011] Furthermore, when the silane monomer is added, a porous carbon loaded with curcumin in an amount of 0.1 to 0.2 times the mass of ethyl 3,3-diphenylpropionate is also added.

[0012] Furthermore, the method for preparing the porous carbon loaded with curcumin comprises: The organic metal salt is calcined under a protective gas atmosphere and then impurities are removed to obtain porous carbon; The porous carbon, curcumin and the second solvent are stirred and mixed at a mass ratio of 2-5:0.5-1:60-80 to obtain the porous carbon loaded with curcumin.

[0013] Furthermore, a soluble cobalt salt in an amount of 0.1 to 0.3 times the mass of the curcumin is added during the stirring and mixing; The second solvent includes at least one of ethanol, acetone, glacial acetic acid and propylene glycol.

[0014] Further, the catalyst includes at least one of an organic tin compound, a titanate compound, and a germanium compound; The first solvent includes at least one of toluene and ethyl acetate; The silane monomer includes at least one of methyldiphenylsilane and tetramethyltetravinylcyclotetrasiloxane.

[0015] Furthermore, the base film resin includes at least one of polypropylene, polyethylene resin, polyvinyl chloride, polytetrafluoroethylene, and thermoplastic polyolefin.

[0016] It should be noted that in the present invention, the type of initiator does not need to be strictly limited, and can be selected as needed, and can trigger a free radical reaction. For example, it can be at least one of diisopropylbenzene peroxide, dibenzoyl peroxide, azobisisobutyronitrile, azobisisoheptylonitrile, potassium persulfate, etc. The porous carbon organic metal salt can be prepared by at least one of a metal citrate, a metal gluconate, a metal tartaric acid, etc., preferably a metal citrate, such as sodium citrate, potassium citrate, zinc citrate, and ferric citrate. Antioxidants and light stabilizers do not need to be strictly limited, and are all raw materials commonly used in the art; antioxidants can be at least one of alcohol esters, phenols, amines, and phosphite antioxidants; light stabilizers can be at least one of hindered phenols, hindered amines, benzophenones, benzotriazoles, and phosphite light stabilizers. Soluble cobalt salts do not need to be limited, and are preferably inorganic cobalt salts, such as at least one of hexahydrated cobalt nitrate and hexahydrated cobalt chloride.

[0017] The present invention also provides a method for preparing the above-mentioned heat-resistant and corrosion-resistant adhesive film, comprising: The base film resin, modified styrene-butadiene rubber, antioxidant and light stabilizer are mixed and then extruded and granulated to obtain a masterbatch; Forming a film from the masterbatch to obtain a film layer; Placing the material of the hot melt adhesive layer on one side of the film layer and then hot pressing and laminating to obtain a heat-resistant and corrosion-resistant adhesive film; The thickness of the film layer and the hot melt adhesive layer is 10-100 μm.

[0018] The present invention also provides a film-covered plate, at least one surface of which is laminated with the above-mentioned heat-resistant and corrosion-resistant adhesive film.

[0019] Compared with the prior art, the present invention has the following beneficial effects: The invention adsorbs and loads curcumin onto porous carbon, and then reacts with styrene-butadiene rubber, perfluorooctyl ethyl acrylate and furfuryl methacrylate to obtain modified styrene-butadiene rubber, which can improve the dispersion performance of porous carbon in a resin matrix, and the porous carbon with good thermal conductivity and strong stability is evenly distributed in a film layer, which can form an effective thermal conductive network to improve the thermal conductivity of the film layer, thereby improving the heat resistance of the film layer.

[0020] Perfluorooctyl ethyl acrylate with fluorocarbon bonds, furanyl methacrylate with furan groups, and porous carbon loaded with curcumin were used for reaction modification with styrene-butadiene rubber. The introduction of fluorocarbon bonds is beneficial to improving the temperature resistance of the film layer; the furan group and the benzene ring of the modified polyester in the hot melt adhesive layer have a certain aromatic ring stacking effect, which can improve the bonding performance of the hot melt adhesive layer and the film layer. DETAILED DESCRIPTION

[0021] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0022] Some of the raw materials used in the examples and comparative examples of the present invention are described as follows: Polypropylene, model YPJ-1215C, sourced from Sinopec Yangzi Petrochemical Co., Ltd.; Styrene-butadiene rubber, model YH-792, sourced from Baling Branch of Sinopec; Perfluorooctyl ethyl acrylate, CAS number is 27905-45-9; Furfuryl methacrylate, CAS number is 3454-28-2; Curcumin, CAS number 458-37-7; The antioxidant is tris (2, 4-di-tert-butylphenyl) phosphite, namely antioxidant 1076, CAS number 2082-79-3; The light stabilizer is tris (1, 2, 2, 6, 6-pentamethylpiperidinyl) phosphite, i.e. light stabilizer GW-540, CAS No. 95733-09-8; Ethyl 3,3-diphenylpropionate, CAS number 7476-18-8; Versatile vinyl carbonate, CAS number is 51000-52-3; Ethylene-vinyl acetate copolymer, brand 18J3, from Beijing Yanshan Petrochemical Co., Ltd. of Sinopec Group; Maleic anhydride grafted polyethylene, model 41E755, comes from Dow Group, USA.

[0023] Other raw materials not mentioned are common raw materials. The above content is only to help illustrate the present invention and shall not be construed as a strict limitation of the present invention. Those skilled in the art can directly purchase the same / similar raw materials from the market or prepare them by themselves. These contents will not be repeated in the examples.

[0024] The following will be combined with the specific embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Example 1 A method for preparing a heat-resistant and corrosion-resistant adhesive film, comprising the following steps: S1. Put 5 kg of polypropylene into an internal mixer and melt it at 165°C, then add 1.5 kg of modified styrene-butadiene rubber, 0.07 kg of antioxidant 1076, and 0.04 kg of light stabilizer GW-540, mix for 20 minutes and then extrude to obtain a masterbatch; S2, putting the masterbatch into a biaxial stretch film machine, heating it to 170°C for melting, and then extruding, stretching, shaping, slitting, and winding to obtain a film layer with a thickness of 100 μm; S3, 2.5 kg of modified polyester, 4 kg of ethylene-vinyl acetate copolymer, and 0.8 kg of maleic anhydride grafted polyethylene were mixed at 80° C. and 80 rpm for 30 min, and then rolled to obtain a hot melt adhesive layer with a thickness of 30 μm; S4. Place a hot melt adhesive layer on one side of the film layer and hot press it at a temperature of 135° C. and a pressure of 0.6 MPa for 10 seconds to obtain a heat-resistant and corrosion-resistant adhesive film.

[0026] Wherein, the preparation method of modified styrene-butadiene rubber is: 4 kg of styrene butadiene rubber was heated to melt at 140° C., and then 0.6 kg of perfluorooctyl ethyl acrylate, 1.2 kg of furfuryl methacrylate, 0.3 kg of porous carbon loaded with curcumin and 0.01 kg of azobisisobutyronitrile were added, and the mixture was reacted at a rotation speed of 80 rpm for 2 h to obtain modified styrene butadiene rubber.

[0027] The preparation method of the porous carbon loaded with curcumin is as follows: T1. 3 kg of zinc citrate was calcined in a muffle furnace at 650 ° C for 2 h in a nitrogen atmosphere. After natural cooling, the inorganic impurities were washed with 2 mol / L hydrochloric acid and then washed with water until the pH of the supernatant was 7.0. The insoluble matter was collected and dried in a constant temperature oven at 120 ° C for 16 h to obtain porous carbon. T2. 30 g of porous carbon, 6 g of curcumin, and 750 g of ethanol were stirred and mixed at a rotation speed of 360 rpm for 6 h, and then the insoluble matter was collected by filtration and transferred to a constant temperature oven at 120° C. for drying for 16 h to obtain porous carbon loaded with curcumin.

[0028] The preparation method of the modified polyester is: 2.5 kg of ethyl 3,3-diphenylpropionate, 6.5 kg of tert-butylene carbonate, and 0.08 kg of azobisisobutyronitrile were added to 12 kg of ethyl acetate, the temperature was raised to 70° C., and the polymerization reaction was carried out under reflux for 5 hours. Then, 8 kg of methyldiphenylsilane and 0.025 kg of dibutyltin dilaurate were added, and the temperature was raised to 90° C. again, and the reaction was carried out under reflux for 2 hours to obtain modified polyester.

[0029] Example 2 The method is basically the same as Example 1, except that: in the preparation method of the modified polyester, when adding methyldiphenylsilane, 0.25 kg of porous carbon loaded with curcumin is also added.

[0030] Example 3 The method is basically the same as Example 1, except that: the preparation method of the porous carbon loaded with curcumin is: T1. 3 kg of zinc citrate was calcined in a muffle furnace at 650 ° C for 2 h in a nitrogen atmosphere. After natural cooling, the inorganic impurities were washed with 2 mol / L hydrochloric acid and then washed with water until the pH of the supernatant was 7.0. The insoluble matter was collected and dried in a constant temperature oven at 120 ° C for 16 h to obtain porous carbon. T2. 30 g of porous carbon, 6 g of curcumin, 1.2 g of cobalt nitrate hexahydrate, and 750 g of ethanol were stirred and mixed at a speed of 360 rpm for 6 h, and then the insoluble matter was collected by filtration and transferred to a constant temperature oven at 120° C. for drying for 16 h to obtain porous carbon loaded with curcumin.

[0031] Example 4 The method is basically the same as Example 3, except that: in the preparation method of the modified polyester, when adding methyldiphenylsilane, 0.25 kg of porous carbon loaded with curcumin is also added.

[0032] Comparative Example 1 A method for preparing an adhesive film, comprising the following steps: S1. 5 kg of polypropylene was put into an internal mixer and melted at 165°C, followed by adding 1.5 kg of modified styrene-butadiene rubber, 0.05 kg of porous carbon, 0.7 kg of antioxidant 1076, and 0.4 kg of light stabilizer GW-540, and the mixture was mixed for 20 minutes and then extruded to obtain a masterbatch; S2, putting the masterbatch into a biaxial stretch film machine, heating it to 170°C for melting, and then extruding, stretching, shaping, slitting, and winding to obtain a film layer with a thickness of 50 μm; S3, 2.5 kg of modified polyester, 4 kg of ethylene-vinyl acetate copolymer, and 0.8 kg of maleic anhydride grafted polyethylene were mixed at 80° C. and 80 rpm for 30 min, and then rolled to obtain a hot melt adhesive layer with a thickness of 30 μm; S4. Place a hot melt adhesive layer on one side of the film layer and hot press for 10 seconds at a temperature of 135° C. and a pressure of 0.6 MPa to obtain an adhesive film.

[0033] Wherein, the preparation method of modified styrene-butadiene rubber is: 4.3 kg of styrene butadiene rubber was heated to melt at 140° C., and then 0.6 kg of perfluorooctyl ethyl acrylate, 1.2 kg of furfuryl methacrylate and 0.01 kg of azobisisobutyronitrile were added, and the mixture was reacted at a rotation speed of 80 rpm for 2 hours to obtain modified styrene butadiene rubber.

[0034] The method for preparing porous carbon is as follows: 3 kg of zinc citrate was calcined in a muffle furnace at 650 °C for 2 h in a nitrogen atmosphere. After natural cooling, the inorganic impurities were washed away with 2 mol / L hydrochloric acid and then washed with water until the pH of the supernatant was 7.0. The insoluble matter was collected and dried in a constant temperature oven at 120 °C for 16 h to obtain porous carbon.

[0035] The preparation method of the modified polyester is the same as that of Example 1.

[0036] Comparative Example 2 A method for preparing an adhesive film, comprising the following steps: S1. 5 kg of polypropylene was put into an internal mixer and melted at 165°C, followed by adding 1.5 kg of modified styrene-butadiene rubber, 0.05 kg of porous carbon, 0.07 kg of antioxidant 1076, and 0.04 kg of light stabilizer GW-540, and the mixture was mixed for 20 minutes and then extruded to obtain a masterbatch; S2, putting the masterbatch into a biaxial stretch film machine, heating it to 170°C for melting, and then extruding, stretching, shaping, slitting, and winding to obtain a film layer with a thickness of 100 μm; S3, 0.01 kg of porous carbon, 2.5 kg of modified polyester, 4 kg of ethylene-vinyl acetate copolymer, and 0.8 kg of maleic anhydride grafted polyethylene were mixed at 80° C. and 80 rpm for 30 min, and then rolled to obtain a hot melt adhesive layer with a thickness of 30 μm; S4. Place a hot melt adhesive layer on one side of the film layer and hot press for 10 seconds at a temperature of 135° C. and a pressure of 0.6 MPa to obtain an adhesive film.

[0037] Wherein, the preparation method of modified styrene-butadiene rubber and porous carbon is the same as that of Comparative Example 1.

[0038] The preparation method of the modified polyester is the same as that of Example 1.

[0039] Comparative Example 3 Compared with Example 4, the difference is that: in the preparation method of the modified styrene-butadiene rubber, no perfluorooctyl ethyl acrylate is added, and 1.8 kg of furfuryl methacrylate is used to replace the absence of perfluorooctyl ethyl acrylate.

[0040] Comparative Example 4 Compared with Example 4, the difference is that: in the preparation method of the modified styrene-butadiene rubber, furfuryl methacrylate is not added, and 1.8 kg of perfluorooctyl ethyl acrylate is used to replace the absence of furfuryl methacrylate.

[0041] Comparative Example 5 Compared with Example 4, the difference is that the porous carbon loaded with curcumin is not added in the preparation method of the modified styrene-butadiene rubber.

[0042] Comparative Example 6 The method is basically the same as Example 1, except that styrene-butadiene rubber is used instead of modified styrene-butadiene rubber.

[0043] Test Case The hot melt adhesive layers of the adhesive films prepared in the examples and comparative examples were bonded to the upper and lower surfaces of a Q235B cold-rolled steel plate with a thickness of 0.5 mm, and then hot-pressed at a temperature of 135° C. and a pressure of 0.6 MPa for 20 seconds to obtain a film-coated plate.

[0044] The peel strength of the film-coated steel sheets at 25°C was tested with reference to the standard T / CBMCA 017-2021 "Film-coated steel sheets for construction". The film-coated steel sheets were placed at 150°C and 90% humidity for 14 days, and the peel strength was tested again. The strength retention rate was calculated to evaluate the heat resistance. The results are shown in Table 1.

[0045] Table 1 Peel strength and heat resistance of laminated boards It can be seen from the test results in Table 1 that the film-coated board constructed by the adhesive film of the embodiment of the present invention has stronger peeling strength and better temperature resistance. Compared with Comparative Example 6 in which porous carbon is not introduced, the peeling strength of Comparative Example 1 in which porous carbon is directly added to the film layer and Comparative Example 2 in which porous carbon is added to the hot melt adhesive layer is reduced. This is because the porous carbon cannot be evenly dispersed in the film layer and the hot melt adhesive layer material. The porous carbon forms agglomerations, which not only makes the bonding between the film layer and the hot melt adhesive layer worse, but also leads to poor connection performance between the hot melt adhesive layer and the steel plate, thereby significantly reducing the peeling strength. In Example 1, styrene-butadiene rubber, perfluorooctyl ethyl acrylate, furfuryl methacrylate, and porous carbon loaded with curcumin are reacted under the action of an initiator to obtain a modified styrene-butadiene rubber and polyethylene to obtain a film material; compared with Example 1, Example 2 further introduces the porous carbon loaded with curcumin into the modified polyester structure, because the porous carbon loaded with curcumin by the polymerization reaction can be well dispersed in the film layer and the hot melt adhesive layer, and can exert its good mechanical properties and thermal conductivity, and also strengthen the interaction between the film layer and the hot melt adhesive layer, thereby significantly improving the peel strength and heat resistance. In Example 3, compared with Example 1, Example 4 is compared with Example 2, and cobalt ions are introduced in the preparation process of the porous carbon loaded with curcumin. The presence of cobalt ions and the polymer can form a more stable structure, and at the same time form a better thermal conductivity network, so the peel strength and heat resistance are further improved. Compared with Example 4, Comparative Example 3 only uses furfuryl methacrylate to modify styrene butadiene rubber; Compared with Example 4, Comparative Example 4 only uses perfluorooctyl ethyl acrylate to modify styrene butadiene rubber; Compared with Example 4, Comparative Example 4 does not add porous carbon loaded with curcumin in the modification of styrene butadiene rubber, and their performances are all reduced. This is because perfluorooctyl ethyl acrylate has fluorocarbon bonds that are beneficial to improving strength and heat resistance; the furan group and the benzene ring of the modified polyester in the hot melt adhesive layer have a certain aromatic ring stacking effect, which can improve the bonding performance of the hot melt adhesive layer and the membrane layer; the introduction of porous carbon loaded with curcumin can synergize with furfuryl methacrylate and perfluorooctyl ethyl acrylate to form a more stable structure.

[0046] According to the standard GB / T 10125-2021 "Artificial atmosphere corrosion test salt spray test", the neutral salt spray resistance test was carried out, and the time when rust spots began to appear on the surface was recorded in days. The results are shown in Table 2.

[0047] Table 2 Neutral salt spray resistance test results It can be seen from the results in Table 2 that the film-coated board constructed by the adhesive film of the embodiment of the present invention has better neutral salt spray corrosion resistance. This is because the stronger bonding strength and the good dispersion of the porous carbon loaded with curcumin in the film layer and the hot melt adhesive layer effectively block the corrosion.

[0048] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A heat-resistant and corrosion-resistant adhesive film, comprising a film layer and a hot-melt adhesive layer, characterized in that: The materials of the film layer include, by weight, 40-60 parts of base film resin, 10-20 parts of modified styrene-butadiene rubber, 0.5-1 parts of antioxidant, and 0.2-0.5 parts of light stabilizer; wherein the modified styrene-butadiene rubber is obtained by reacting styrene-butadiene rubber, perfluorooctyl ethyl acrylate, furfuryl methacrylate, and porous carbon loaded with curcumin under the action of an initiator; The materials of the hot melt adhesive layer include, by weight, 10 to 30 parts of modified polyester, 30 to 50 parts of ethylene-vinyl acetate copolymer, and 5 to 10 parts of maleic anhydride grafted polyethylene.

2. The heat-resistant and corrosion-resistant adhesive film according to claim 1, characterized in that: The preparation method of the modified styrene-butadiene rubber comprises, by parts by mass, 30-50 parts of styrene-butadiene rubber are heated and melted, and then 5-10 parts of perfluorooctyl ethyl acrylate, 10-15 parts of furfuryl methacrylate, 2-5 parts of porous carbon loaded with curcumin and 0.5-1.5 parts of initiator are added to react to obtain modified styrene-butadiene rubber.

3. The heat-resistant and corrosion-resistant adhesive film according to claim 1, characterized in that: The preparation method of the modified polyester comprises, by parts by mass, 10-30 parts of ethyl 3,3-diphenylpropionate, 50-80 parts of versatate vinyl carbonate and 0.2-1 parts of initiator are added to 60-150 parts of the first solvent for polymerization reaction at elevated temperature, and then 60-100 parts of silane monomer and 0.1-0.3 parts of catalyst are added for further reaction at elevated temperature to obtain modified polyester.

4. The heat-resistant and corrosion-resistant adhesive film according to claim 3, characterized in that: When the silane monomer is added, a porous carbon loaded with curcumin in an amount of 0.1 to 0.2 times the mass of 3,3-diphenylpropionate is also added.

5. The heat-resistant and corrosion-resistant adhesive film according to claim 4, characterized in that: The method for preparing the porous carbon loaded with curcumin comprises: The organic metal salt is calcined under a protective gas atmosphere and then impurities are removed to obtain porous carbon; The porous carbon, curcumin and the second solvent are stirred and mixed at a mass ratio of 2-5:0.5-1:60-80 to obtain the porous carbon loaded with curcumin.

6. The heat-resistant and corrosion-resistant adhesive film according to claim 5, characterized in that: During the stirring and mixing, 0.1 to 0.3 times the mass of curcumin is added with a soluble cobalt salt; The second solvent includes at least one of ethanol, acetone, glacial acetic acid and propylene glycol.

7. The heat-resistant and corrosion-resistant adhesive film according to claim 3, characterized in that: The catalyst comprises at least one of an organic tin compound, a titanate compound, and a germanium compound; The first solvent includes at least one of toluene and ethyl acetate; The silane monomer includes at least one of methyldiphenylsilane and tetramethyltetravinylcyclotetrasiloxane.

8. The heat-resistant and corrosion-resistant adhesive film according to claim 1, characterized in that: The base film resin includes at least one of polypropylene, polyethylene resin, polyvinyl chloride, polytetrafluoroethylene, and thermoplastic polyolefin.

9. A method for preparing a heat-resistant and corrosion-resistant adhesive film according to any one of claims 1 to 8, characterized in that: include, The base film resin, modified styrene-butadiene rubber, antioxidant and light stabilizer are mixed and then extruded and granulated to obtain a masterbatch; Forming a film from the masterbatch to obtain a film layer; Placing the material of the hot melt adhesive layer on one side of the film layer and then hot pressing and laminating to obtain a heat-resistant and corrosion-resistant adhesive film; The thickness of the film layer and the hot melt adhesive layer is 10-100 μm.

10. A film-faced board, characterized in that: At least one surface is bonded with the heat-resistant and corrosion-resistant adhesive film according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • ASA (Acrylonitrile Styrene Acrylate) hot-sticking composite film and preparation method thereof as well as film-coated plate and preparation method thereof

    CN118667282A

  • Enhanced wear-resistant cross-linked integrated backboard and production method thereof

    CN110183745A

  • Boiling-resistant polyethylene hot melt adhesive composition for aluminum-plastic panel as well as preparation method and application of boiling-resistant polyethylene hot melt adhesive composition

    CN114621706A

  • Multifunctional film-coated plate and preparation method thereof

    CN115570864A